Electrochemical Oxygen Generator With 99.9% Oxygen Purity and High Energy Efficiency. Issue 29 (23rd June 2022) - Zhang, Yu; Xie, Ke; Zhou, Fangyao; Wang, Feiteng; Xu, Qian; Hu, Jun; Ding, Honghe; Li, Peng; Tan, Yi; Li, Deming; Zhu, Junfa; Zhou, Huang; et al.
Abstract: Under the growing crisis of the coronavirus disease 2019 pandemic, the global medical system is facing the predicament of an acute shortage of medical‐grade oxygen (O2, ≥ 99.5% purity). Herein, an oxygen generation device is manufactured that relies on electrochemical technology. The performance of the electrochemical oxygen generator (EOG) is remarkably improved to a practically applicable level, achieving long‐term (>200 h), stable, and quick production (>1.5 L min −1 ) of high purity O2 (99.9%) at high energy efficiency (496 L kW −1 h −1 ), via simultaneous optimization for intrinsic electrochemical reaction mechanisms, electrocatalysts, and external cell structure. The EOG also presents powerful competitiveness in user experience, which finds expression in high portability (4.7 kg), nearly instant O2 production (<1 s), and a quiet working condition (<39 dB). The EOG shows great potential to substitute commercial pressure swing adsorption O2 generation devices, which may significantly impact the traditional oxygen production industry. Abstract : Electrochemical technology is applied for fabricating an electrochemical oxygen generator (EOG), which realizes stable (>200 h), portable (4.7 kg), energy‐saving (496 L kW −1 h −1 ), quiet (<39 dB), rapid (<1 s) and in situ production of oxygen with 99.9% purity. The fabricated EOG shows great potential to substitute commercial pressure swing adsorption oxygen generation devices, which may significantly impact the traditional oxygen production industry.